Sosialisasi Kurikulum Merdeka Belajar Pada Guru-Guru di SD Inpres Tomra di Wilayah Daerah 3T (Terdepan, Terpencil Dan Tertinggal) - Sefanya Sairiltiata; Melati Umarella; Dovila Johansz; Jekriel Septory (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The presence of this independent learning curriculum is a challenge in itself for teachers in 3T (Frontier, Remote and Disadvantaged) areas, including at SD Inpres Tomra, which is an area classified as a border area. Frontier, Remote and Disadvantaged Regions are the outermost regions in Indonesia, basically there are 122 regions in Indonesia that are included in the 3T region, one of which is Southwest Maluku Regency, Pulau Letti District. The aim of community service is to add new understanding to the teachers at SD Inpres Tomra regarding the application and implementation of the independent learning curriculum in elementary schools. Methods Used This community service activity is carried out based on the following stages: Pre-activity, 2). Implementation of Activities, 3). Post-Activity. Teachers in border areas, especially at SD Inpres Tomra, really need socialization about the independent curriculum so they can increase their insight and knowledge about the implementation of the independent learning curriculum. Based on the results of the socialization carried out, there is an increase in teacher understanding and in-depth knowledge about the independent learning curriculum and its implementation in elementary schools so that the learning process can run effectively and efficiently.